El català al País Valencià: retracció i resistència - Pitarch, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: The use of Catalan has been restricted to rural areas in the País Valencià. This fact hinders it form becoming an adequate language for communication in our present industrial society. The author proposes the active linguistic fidelity to improve this situation.